Blackhood Against the Police Power : Punishment and Disavowal in the "Post-Racial" Era - Woods, Tryon P. (Book collections on Project MUSE., 2019)
Both significant and timely, Blackhood Against the Police Power addresses the punishment of "race" and the disavowal of sexual violence central to the contemporary "post-racial" culture of politics. Here the author asserts that the post-racial presents an antiblack animus that should be read as desiring the end of blackness and the black liberation movement's singular ethical claims. The book redefines policing as a sociohistorical process of implementing antiblackness and, in so doing, redefines racism as an act of sexual violence that produces the punishment of race. It smartly critiques the way leading antiracist discourse is frequently complicit with antiblackness and recalls the original 1960s conception of black studies as a corrective to the deficiencies in today's critical discourse on race and sex. The book explores these lines of inquiry to pinpoint how the history of racial slavery wraps itself in a new discourse of disavowal. In this way, Blackhood Against the Police Power responds to a range of texts, policies, practices, and representations complicit with the police power--from the Fourth Amendment and the movements to curtail stop-and-frisk policing and mass incarceration to popular culture treatments of blackness to the leading academic discourses on race and sex politics.--Publisher website.